Serum vitamin D and vitamin D receptor gene FokI polymorphisms in children with tuberculosis - Ariesta Karmila; Muhammad Nazir; Kiagus Yangtjik; Yuwono Yuwono (Paediatrica Indonesiana, 2015)
Background Vitamin D deficiency and vitamin D receptor (VDR) gene polymorphisms are strongly associated with tuberculosis (TB) susceptibility in countries with four seasons. As a country with sufficient sunlight for vitamin D production in skin, the incidence of TB in Indonesia remains high. Objective To assess for possible associations between the incidence of tuberculosis and serum vitamin D level, as well as VDR FokI polymorphisms in children. Methods A case-control study was conducted at the Department of Child Health, Dr. Mohammad Hoesin Hospital, Palembang from November 2011 to April 2012. Subjects were children with TB (the case) and children without TB who had been exposed to TB in the home (the control). Serum vitamin D [1,25(OH)2D3 or calcitriol] level was measured by immunodiagnostic system (IDS) 1,25-dihydroxy vitamin D enzyme immunoassay (EIA) kit. The VDR FokI polymorphisms were identified by polymerase chain reaction (PCR) and restriction-fragment length polymorphism (RFLP) analysis. Results Sixty subjects was divided equally into the case and control groups. The mean serum calcitriol level in the case group was significantly lower than that of the control group [105.5 (SD 66.9) pmol/L vs. 162.9 (SD 52.9) pmol/L, respectively; (P=0.001)]. We found 9 subjects with calcitriol deficiency, 8 in the TB group and 1 in the healthy contact group (OR 10.5; 95%CI 1.2 to 90.7) The VDR FokI polymorphism was seen in 28 subjects in the case group and 22 in the control group (OR 5.0; 95%CI 0.9 to 26.4). Conclusion Vitamin D (calcitriol) deficiency and lower serum levels are associated with higher risk of TB in children. The VDR gene FokI polymorphism also contributes to susceptibility for TB.